Comparative study of Central, East European, Baltic and Turkish economies with a view to future membership to European Union - Togan, Subidey (Cairo Economic Research Forum for the Arab Countries Iran & Turkey, 1995)
The purpose of this paper is to comparatively study the Central European Economies (CEE), Baltic and Turkish economies and to analyze the implications of enlargement of the European Union (EU) to include them. Integration will depend on these countries' ability to make their economies responsive to market forces. Recognizing international trade as an effective means to instill competition in these countries, the paper studies trade policy in the CEE and Baltic countries and in Turkey and the trade agreements concluded between these countries and the EU. In particular, the Turkey-EU Customs Union Agreement (CUA) and Europe Agreements (EA) are studied and the potential for trade between EU, CEE and Baltic countries and Turkey is considered. In a discussion of these countries' chances for EU membership, we emphasize that the EU has to evaluate the budgetary outlays of membership relative to potential gains which would come in terms of increased trade and political stability الغرض من هذه الورقة هو اجراء دراسة مقارنة بين اقتصادات اوروبا الشرقية ودول البلطيق وتركيا وتحليل آثار توسيع الاتحاد الاوروبى ليضم فى عضويته هذه الدول. وسوف يتوقف انضمام هذه الدول على قدرة اقتصاداتها على الاستجابة لقوى السوق وتسليما بأن التجارة الدولية أداة فعالة لتعزيز المنافسة بين الدول؛ تبحث الورقة السياسة الاقتصادية فى الاتحاد الاوروبى ودول البلطيق وتركيا؛ وتحلل الاتفاقات التجارية المعقودة بين هذه الدول والاتحاد الاوروبى؛ولاسيما اتفاق الاتحاد الجمركى بين تركيا والاتحاد الاوروبى واحتمالات التجارة بين الاتحاد الاوروبى واقتصادات اوروبا الشرقية ودول البلطيق وتركيا. وفى مناقشة لفرص التحاق هذه الدول بعضوية الاتحاد الاوروبى نوضح أن على الاتحاد أن يجرى تقييما للالتزامات فى ميزانيته بالقياس الى المكاسب المحتملة التى تتحقق فى صورة زيادة للتجارة وتحقيق الاستقرار السياسى.
Includes bibliographical references
Keywords: International economics; INTERNATIONAL ECONOMY; FOREIGN DIRECT INVESTMENT; TURKEY; Baltic States; Central and Eastern Europe; Europe, Central; EUROPEAN FEDERATION; Economic Research Forum